Short Communication: Fish diversity of the Batang Toru River System, South Tapanuli, North Sumatra - DEWI IMELDA ROESMA; ADA CHORNELIA; AHMAD MURSYID; MISTAR KAMSI (Society for Indonesian Biodiversity, 2016)
Roesma DI, Chornelia A, Mursyd A, Kamsi M. 2016. Short Communication: Fish diversity of the Batang Toru River System, South Tapanuli, North Sumatra. Biodiversitas 17: 628-634. A rapid survey on fish diversity was carried in the Batang Toru river system. The survey was carried out in the wet season between 8-14 February 2015 and 15-21 of March 2015 along various tributaries on the east (10) and west (1) side of the main Batang Toru river system. We obtained 427 individuals fish samples consisting of 24 species, from 10 families. These consist of Cyprinidae (11 species), Balitoridae (2), Channidae (2), Gobiidae (2), Nemacheilidae (2), Aplocheilidae (1), Bagridae (1), Cichlidae (1), Mastacembelidae (1), and Sisoridae (1). Four Sumatra fish species were encountered during the surveys, namely Neolissochilus sumatranus, Nemacheilus pfeifferae, Homaloptera gymnogaster and H. heterolepis. N. sumatranus and Puntius binotatus were the most frequently found in all of sampling sites.